The Europeanization of Europe: The transfer of norms to Europe, in Europe and from Europe - Trine Flockhart (Danish Institute for International Studies (DIIS), 2008)
Europeanization is a concept predominantly concerned with the domestic impact of the EU whilst less concerned with its historical foundations and wider geographical reach. By forwarding a Historical Sociological conceptualization of Europeanization it is revealed that the concept suffers from fundamental problems relating to historical and geographical scope, to uncertainty about which causal relationships to explain, and that it is based on implicit but unsustainable assumptions. This article challenges the assumption that Europeanization is based on ideas endogenous to Europe and is an activity preserved for Europeans. It suggests that 'Europeanization' can be conceptualized as several social processes involving different agents, structures, processes and conceptions of 'self' and 'other', and that Europeans have been more on the receiving end of ideational diffusion than promoters of a European norm set. By employing a Historical Sociological perspective it is revealed that before Europeans could 'Europeanize' either in or from Europe, they not only had to develop a European identity through a process of ideational diffusion to Europe, but the idea set which is today regarded as 'European' was diffused from the United States and stands in complete contrast to ideas previously also regarded as European.
Keywords: 330; Soziologie; Geschichte; Soziale Norm; Europa